2004
DOI: 10.1530/rep.1.00220
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro differentiation of male germ cells in the mouse

Abstract: Primordial germ cells appear in the embryo at about day 7 after coitum. They proliferate and migrate towards the genital ridge. Once there, they undergo differentiation into germ stem cells, known as 'A spermatogonia'. These cells are the foundation of spermatogenesis. A spermatogonia commit to spermatogenesis, stay undifferentiated or degenerate. The differentiation of primordial germ cells to migratory, postmigratory and germ stem cells is dependent on gene expression and cellular interactions. Some of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 50 publications
6
80
0
4
Order By: Relevance
“…8 Loss of Mvh function causes a deficiency in the proliferation and differentiation of male germ cells. 22 These results indicate that a subpopulation of BSCderived cells can be characterized as PGCs.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…8 Loss of Mvh function causes a deficiency in the proliferation and differentiation of male germ cells. 22 These results indicate that a subpopulation of BSCderived cells can be characterized as PGCs.…”
Section: Resultsmentioning
confidence: 76%
“…Furthermore, we used RT-PCR to detect expression of fragilis, stella, Mvh; and Rnf17 genes, which are expressed in early stage of male germ cell development. [6][7][8]22 All four genes were expressed in BMS-GC, but not in untreated BMS (Figure 4). Fragilis is the first gene to mark the onset of germ cell competence, and it follows Differentiation of MSC to male germ cells K Nayernia et al a pattern consistent with the eventual segregation of germ cells from allantoic precursors.…”
Section: Resultsmentioning
confidence: 99%
“…These observations are in contrast to the older assumption that early follicles are completely gonadotropin independent [51]. Furthermore, two recent publications found that the proliferation of primordial germ cells is gonadotropin dependent and is mediated by Akt/phosphatase and tensin homologue deleted on chromosome ten (PTEN) signaling [54,55]. High concentrations of estrogens stimulate mouse primordial germ cell growth in vitro through the somatic cells of the gonad [54,55].…”
Section: I: Interruption Of Follicle-stimulating Hormone Secretionmentioning
confidence: 89%
“…Morphologically, spermatogonial stem cells are smaller than their sexually undifferentiated progenitor PGCs and possess distinctive microstructures (7). Furthermore, the differentiation of mouse PGCs into spermatogonial stem cells alters the expression of various genes, including alkaline phosphatase, c-kit (8), nanos homologue 2 (nanos2), and nanos homologue 3 (nanos3) (9). Yet it remains unclear how these shifts in gene expression induce functional differences between vertebrate PGCs and spermatogonial stem cells.…”
mentioning
confidence: 99%